2015
DOI: 10.1001/jamaophthalmol.2015.0477
|View full text |Cite
|
Sign up to set email alerts
|

Scotopic and Photopic Microperimetry in Patients With Reticular Drusen and Age-Related Macular Degeneration

Abstract: IMPORTANCE Clinical observations suggest that patients with age-related macular degeneration (AMD) have vision problems, particularly in dim light conditions. Previous studies on structural-functional analysis in patients with AMD with reticular drusen (RDR) have focused on photopic sensitivity testing but have not specifically assessed scotopic function. OBJECTIVE To evaluate retinal function by scotopic and photopic microperimetry in patients with AMD and a well-demarcated area of RDR. DESIGN, SETTING, AND P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 43 publications
(59 reference statements)
9
83
2
Order By: Relevance
“…Later, it was demonstrated that scotopic sensitivity loss exceeded photopic sensitivity impairment in areas with increased levels of fundus autofluorescence [31] . Secondly, the no longer commercially available scanning laser ophthalmoscope (SLO 101, Rodenstock, Ottobrunn, Germany) has been used for scotopic FCP; however, only a single congress abstract has been available so far to the best of our knowledge [ While many reports on mesopic function with the MP-1 device are available, only a few reports have been published on scotopic FCP using the MP-1S [20,21,24,[32][33][34][35] . For example, we have recently shown that the presence of reticular drusen is spatially confined to outer retinal thinning and impairment of scotopic function [21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was demonstrated that scotopic sensitivity loss exceeded photopic sensitivity impairment in areas with increased levels of fundus autofluorescence [31] . Secondly, the no longer commercially available scanning laser ophthalmoscope (SLO 101, Rodenstock, Ottobrunn, Germany) has been used for scotopic FCP; however, only a single congress abstract has been available so far to the best of our knowledge [ While many reports on mesopic function with the MP-1 device are available, only a few reports have been published on scotopic FCP using the MP-1S [20,21,24,[32][33][34][35] . For example, we have recently shown that the presence of reticular drusen is spatially confined to outer retinal thinning and impairment of scotopic function [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Another modified version of MP-1 has also been used for fundus-controlled two-color perimetry and dark adaptometry [36,37] . However, the dynamic range of the stimulus-presenting LCD display of the MP-1 (20 dB) is considered to be low and prone to ceiling and floor effects in both mesopic and scotopic examinations [20,32,33] . Moreover, the quality of the reference image (infrared fundus camera) has been reported to be low, making reliable detection of retinal pathologies and test pattern placement challenging [38] .…”
Section: Introductionmentioning
confidence: 99%
“…16,[19][20][21] In these studies, rod function was assessed after a period of dark-adaptation either with or without preceding photobleach. Given that there is increased interests in using a scotopic perimeter for monitoring AMD progression in clinical studies and drug trials it is important to determine which perimetric testing method is superior in detecting rod abnormality and functionally characterizing the disease phenotype in eyes with AMD.…”
mentioning
confidence: 99%
“…In a recent, exploratory study of 20 patients with advanced AMD, they found scotopic microperimetry to be the best predictor of patient-reported difficulties under low light as measured by the Low Luminance Questionnaire (LLQ). In patients with iAMD, localized scotopic dysfunction is more pronounced compared to mesopic dysfunction in areas with reticular drusen, a risk factor for AMD progression [22]. Preparatory assessments showed that where early scotopic microperimeters had problems with testing accuracy, speed, and acceptability to patients, the scotopic MAIA (S-MAIA, Centervue, Italy) is easier to operate, with less operator-induced variability.…”
Section: Resultsmentioning
confidence: 99%